Edible Coating Berbasis Pati Ubi Kayu Manihot esculenta Crantz dan Jahe Merah Zingiber officinale var. rubrum Memperpanjang Umur Simpan Buah Tomat Solanum lycopersicum L. - JOHANNES, EVA; TUWO, MUSTIKA; KATAPPANAN, NATALIA; HENRA, HENRA; WIRIANTI, GUSNI (Agrotrop : Journal on Agriculture Science; Vol 12 No 2 (2022)DO - 10.24843/AJoAS.2022.v12.i02.p03, 2022)
Edible Coating based on Cassava Starch Manihot esculenta Crantz and Red Ginger Zingiber officinale var. rubrum Extends Shelf Life of Tomato Fruit Solanu lycopersicum L. Packaging with edible coating is one of the efforts developed to overcome soft rot in fruit, especially cut fruit such as tomatoes, Solanum lycopersicum L. This study aims to test natural preservatives for cut fruit through edible coatings with the addition of active compounds that have antioxidants and antifungals that can extend the shelf life of tomatoes. The method used for coating is starch-based edible coating with the addition of red ginger extract Zingiber officinale var. rubrum. Rhizoma as a bioactive compound that has antimicrobial and antioxidant properties. Soaking the samples using the edible coating method with distilled water, 0.4% CMC (carboxy methyl cellulose) solution and 5% glycerol, 4% cassava starch, and 0.1% red ginger extract. The treatments consisted of control (without treatment), coating with cassava starch-based edible coating, and edible coating with the addition of red ginger extract and storage time (3, 6 and 9 days). During the storage period, weight loss and texture tests were carried out. The results of the edible coating test with the addition of ginger extract are fungicidal against the fungus Aspergillus niger , had strong antioxidant properties with an IC 50 value of 82.55 ppm and had the lowest weight loss in the edible coating treatment with the addition of ginger extract of 3.58% on day 9. The best texture in the edible coating treatment with the addition of ginger extract was 1.87 N on the 9 th day . These results showed that edible coating based on cassava starch with the addition of 0.1% ginger extract was able to increase the shelf life of tomato Solanum lycopersicum L. for 9 days at room temperature.